Physico-chemical characterization and antioxidant capacity of the colombian berry (Vaccinium meridionale Swartz) with a high-polyphenol content: potential effects in people with metabolic syndrome (2019)
ABSTRACT: Colombian berry (agraz) has demonstrated a high antioxidant content in vitro. In the present study, it was elaborated and characterized an agraz nectar, designed a placebo with similar physicochemical and sensorial characteristics of the agraz nectar, but without polyphenols; and evaluated their antioxidant capacity both in vitro and in vivo in adults with cardiovascular risk factors. The polyphenolic concentration of the agraz nectar and its antioxidant capacity was superior than other reported for this fruit. A high content of total cyanidins was observed in the freeze-dried agraz, but not delphinin was detected by HPLC. For the intervention study, sixty-six subjects, with at least three cardiometabolic risk factors, consumed agraz nectar or placebo daily during 4 weeks each, separated by a 4-week washout period. Total phenol concentration and antioxidant capacity in the participants’ serum were not statistically different after consuming agraz nectar and placebo. However, women increased significantly their serum DPPH scavenging capacity after consuming agraz nectar, compared to placebo. This is one of the first studies showing data about the effects of this colombian berry on the antioxidant capacity in people with metabolic syndrome.